Pembuatan Grease Dari Minyak Biji Karet: Pengaruh Campuran LiOHNaOH Dan Rasio Base Oil:Thickening Agent Terhadap Karakteristik Grease - Yolanda, Putri Gusti; Irdoni, Irdoni; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Greases were used to reduce friction between two opposite moving metal surface. The utilized base oil could be vegetable oil and mineral oil, however mineral oil is not environmental friendly. This research objectives was to produce grease from rubber seed oiland to study LiOH-NaOH mole ratio effect and base oil mass ratio effect toward produced grease characteristic. This research pretreatment consisting few steps: raw material preparation involve rubber seed oil extraction by expression, degumming, centrifugation andthen oil characteristic test including density, viscosity and GC-MS. The process continued by LiOH-NaOH metal soap making utilizing rubber seed oil with mole variations (90:10), (80:20) and (70:20), stirring time 30 minutes, stirring speed 650 rpm and stirringtemperature is 70 oC. The last step was blending among base oil, thickening agent and additive with rasio (75:20:5)%w/w, (77,5:17,5:5)%w/w, (80:15:5)%w/w, (82,5:12,5:5)%w/w,(85:10:5)%w/w, stirring time 240 minutes, stirring speed 650 rpm and stirring temperature 120 oC. Rubber seed oil characterization results were density of 0,819 gr/ml and fatty acid content which dominated by unsaturated fatty acid namely linoleic acid 34,11% and linolenic acid 30%. The optimum ratio obtained were LiOH:NaOH ratio of 90%:10% (A1) and base oil:thickening agent:additive of (75:20:5)%w/w with penetration 228 (25 oC), dropping point 125 oC and NLGI number 3.Keywords: dropping point, grease, metal soap, penetration, rubber seed oil.